Hitler, the Germans and the final solution - Kershaw, Ian, 1943- 1943- (Yale Univ. Press [u.a.], 2008)
This volume presents a comprehensive, multifaceted picture both of the destructive dynamic of the Nazi leadership and of the attitudes and behavior of ordinary Germans as the persecution of the Jews spiraled into total genocide.